The Influence of the Activities of the Rohis Extracurricular Organization on the Morals of Learners (Research in MAN Kiarakuda, Ciawi District, Tasikmalaya Regency) - Ilham Arif Pebriansyah; Tatang Muh Nasir; Arief Agus Triansyah (MANAZHIM, 2023)
The problem that arises is whether there is a positive influence from the activities of the Rohis extracurricular organization on the morals of students at MAN Kiarakuda, Ciawi District, Tasikmalaya Regency? This study aims to determine the effect of the activities of the Rohis extracurricular organization on the morals of students at MAN Kiarakuda, Ciawi District, Tasikmalaya Regency. With this aim, this research can be useful for the development of religious knowledge and prayer through intermediaries and its benefits for one of the morals of students. The method used in this research is descriptive method through a quantitative approach, namely research that seeks to reveal the current conditions/conditions by considering the past through questionnaires, interviews, as well as observation and processing of the figures obtained from the research. Based on the results of data processing, it was found that the activities of the Rohis MAN Ciawi extracurricular organization were classified as low. This is indicated by the average value ("X" ̅) = 70 when confirmed to the interpretation scale which is between 68.08 – 72.1 with a good classification. While the morals of the students are classified as good with an average score ("X" ̅) = 70.4 if confirmed on an interpretation scale between 68.8 – 72. And the influence of the activities of the Rohis extracurricular organization on the morals of students at MAN Kiarakuda has an influence significantly with the very high category, with rs = 0.9 in the interval 0.81-1.00 and t_(count ) > t_table 9 > 2.021 so that Ha is accepted and Ho is rejected. Rohis extracurricular organizational activities affect the morals of students by 81% and the remaining 19% are thought to be influenced by other factors, for example the teacher's personality, living environment and others.